The Benefits of Empon-Empon and Gembili Bulbs and Testing the Level of Likeability of Processed Products - Dwiyati Pujimulyani; Bayu Kanetro; Sri Winarti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Most Indonesian people do not know the benefits of some local food ingredients, namely empon-empon and gembili tubers. Empon-empon contains antioxidants such as polyphenols, while gembili tubers contain inulin. Empon-empon can be processed into an instant powder product which is practical for consumption. Gembili tubers can be processed to be flour and then used it as cookies ingredient. This service activity is in the form of counseling on the benefits of empon-empon and gembili tubers, as well as how to process them. The activity partners are the management of Himatepa and HMPPI within UMBY and UPN "Veteran" East Java. Counseling activities was held on Saturday, August 27th, 2022 online via the zoom meeting platform. Methods for processing instant empon-empon powder and gembili cookies were shared via video on Friday, September 2nd, 2022. Tests for the level of preference for instant empon-empon powder and gembili cookies were carried out on Monday, September 5th, 2022 and Friday, September 9th, 2022. Standards sensory test scores are 1 = really dislike, 2 = don't like, 3 = like, 4 = prefer, 5 = like very much. The instant powdered empon-empon products of white turmeric, yellow turmeric, and gembili cookies were favored by the panelists with scores of 4.11, 4.17 and 4.09, respectively. These results provide a high potential for further dissemination to the community.